2004
DOI: 10.1007/s00467-004-1672-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes of blood pressure and left ventricular mass in pediatric renal transplantation

Abstract: Cardiovascular events are among the most frequent causes for long-term morbidity and mortality in children after renal transplantation. The aim of this study was to analyze the effects of post-transplant changes in arterial hypertension, as assessed by 24-h ambulatory blood pressure measurement (ABPM), on myocardial architecture, as assessed by echocardiography. In a retrospective chart review analysis, 39 children were identified in whom 24-h ABPM and echocardiography had been assessed within a 3-month interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
4
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 14 publications
5
41
4
2
Order By: Relevance
“…The glomerular filtration rate (GFR) was computed using the Schwartz formula [GFR (ml/min/ 1.73 m 2 )=0.55×body length (cm)/serum creatinine (mg/dl)]. The blood-pressure index was computed by dividing the mean patient values of the last 24-h ambulatory blood pressure measurement (ABPM) by the 95th percentiles based on the reference values for mid-European children [12]. The standard deviation scores (SDS) of height were calculated ([observed height of the patient−expected height for age]/standard deviation of the mean height for age) for the first day of transplantation and the last day of follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…The glomerular filtration rate (GFR) was computed using the Schwartz formula [GFR (ml/min/ 1.73 m 2 )=0.55×body length (cm)/serum creatinine (mg/dl)]. The blood-pressure index was computed by dividing the mean patient values of the last 24-h ambulatory blood pressure measurement (ABPM) by the 95th percentiles based on the reference values for mid-European children [12]. The standard deviation scores (SDS) of height were calculated ([observed height of the patient−expected height for age]/standard deviation of the mean height for age) for the first day of transplantation and the last day of follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Other groups have reported a high prevalence of LVH in children after renal transplantation, but at least half of the patients were hypertensive, and some also had marked anemia [5,7]. The majority of the patients described in these reports were on cyclosporine-based immunosuppression, and all of the studies were cross-sectional.…”
Section: Lvmi Sds Pre and Post Transplantmentioning
confidence: 96%
“…Left ventricular hypertrophy (LVH) is the most common cardiac abnormality observed in pediatric and adult dialysis patients, and has been associated with hypertension and volume overload [3]. However, LVH is prevalent even after successful RTx, in between 7% and 82% of children in various cross-sectional studies [4][5][6][7][8]. LVH is a significant risk factor for cardiovascular mortality, both in the general population and in patients with renal disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…A Midwest Pediatric Nephrology Consortium study, 21 utilizing data from six centers, demonstrated the prevalence of LVH to be 40% in children 1-year post-transplant. Most of these studies show the persistence of cardiac hypertrophy, [32][33][34] but some report improvement post-transplant. 35 As in adults, hypertension is the main cause of cardiac hypertrophy in children before ESRD or post-transplant.…”
Section: Lvh Is the Most Common Cardiac Abnormality In Children With Ckdmentioning
confidence: 99%